Identification of novel biomarkers for lung cancer risk in high levels of radon by proteomics: A pilot study - N. Autsavapromporn (2020)
© 2019 The Author(s). Radon is the second most important risk factor for lung cancer after tobacco smoking. In Chiang Mai, Thailand, the values of indoor radon activity concentrations are considerably higher than global average values and it is a highest level among East Asian countries. The aim of our study is to identify novel biomarkers for lung cancer risk in high radon areas using a proteomic approach. In our transitional study, a total of 81 participants of non-smokers were examined, consist of 25 lung cancer patients (LC), 16 healthy controls from low levels of natural radiation areas (LLNRA) and 40 healthy controls from high levels of natural radiation areas (HLNRA). The results showed that a total of 799 differentially expressed proteins were identified. Among these, a total of 25 proteins were observed in both LC and HLNRA, but not in LINRA. Owing to the results obtained from this study, we also point out the research direction regarding the validation of some new candidate protein as a biomarker to screen population with high risk for lung cancer in the area with high levels of radon.